A Radiological Assessment of the Prevalence of Osteoporosis in Male Patients Seen in a South African Hospital: A Retrospective Analysis. (4th May 2022) - Siwela, Lebohang; Khan, Nausheen; Mudau, Adziambei
Abstract : Developing countries are predicted to bear the burden of osteoporosis in the coming decades. The prevalence of osteoporosis in South African men is unknown, but is thought to be rare. Opportunistic screening for osteoporosis can be performed using quantitative computed tomography (CT) obtained for various clinical indications. We assessed the frequency of osteoporosis in male patients using quantitative computed tomography (CT) obtained for various clinical indications. Data were collected from abdominal and spinal CT scans performed at the radiology department of a provincial tertiary hospital between January 2019 and January 2021. The CT examinations were derived from 507 male patients (mean age, 45±15 years; 83% Black, 0.8% Coloured, 4.1% Indian and 11.2% White). In the CT scans, the region of interest was placed manually at the axial cross-sections of L1 and L3 vertebrae. Using densitometry, we calculated average bone mass density and T and Z scores. We diagnosed osteoporosis in 18.5% ( n = 94) of our patients. Only 7.9% of patients younger than 50 had osteoporosis, while 35.9% of patients older than 50 years showed signs of osteoporosis. Osteoporosis was more common amongst White male patients (45.6%) and least common in Black male patients (14.4%). Indian patients had the highest prevalence of osteopenia (42.9%). We successfully used CT scans, obtained for various conditions, to identify large numbers of patients with low bone mineral density (BMD). The prevalence of osteoporosis in this sample is similar to rates reported elsewhere in Africa. Asymptomatic patients at risk of developing insufficiency fractures can be diagnosed and managed early using CT scans, thus preventing unnecessary admissions and reducing osteoporosis-related morbidity and mortality.